1972
DOI: 10.1126/science.175.4023.789
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Increase of Phenylethanolamine N -Methyltransferase by Environmental Stress in an Inbred Mouse Strain

Abstract: The activity of-phenylethanolamine N-methyltransferase in mice of the C57Bl/Ka strain was determined after a 4 degrees C stress. The enzyme activity increased 1.2-fold at the end of 3 hours and by 1.4-fold by the end of 6 hours of the stress. The results are in contrast to those from other species with intact animals in which the enzyme changes only after several days of chronic stress. Cycloheximide prevents the rise in enzyme activity, suggesting the increase may be due to protein synthesis. The increase may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…A single immobilization stress causes a small but significant increase (50%) in adrenal PNMT activity, which is not elevated further even after repeated immobilizations . A similar increase in adrenal PNMT activity is elicited by exposure of animals to cold stress (Ciaranello et al ., 1971 ;Kvetnansky et al ., 1971a), but the changes in PNMT activity are generally smaller than those of the other enzymes involved in catecholamine biosynthesis (reviewed by Kvetnansky and Sabban, 1993) . However, the changes in PNMT gene expression during stress have not been studied extensively .…”
mentioning
confidence: 55%
“…A single immobilization stress causes a small but significant increase (50%) in adrenal PNMT activity, which is not elevated further even after repeated immobilizations . A similar increase in adrenal PNMT activity is elicited by exposure of animals to cold stress (Ciaranello et al ., 1971 ;Kvetnansky et al ., 1971a), but the changes in PNMT activity are generally smaller than those of the other enzymes involved in catecholamine biosynthesis (reviewed by Kvetnansky and Sabban, 1993) . However, the changes in PNMT gene expression during stress have not been studied extensively .…”
mentioning
confidence: 55%
“…All studies were performed in male mice, age [11][12][13][14] weeks. Balb/cJ mice were obtained from the Jackson Laboratories, Bar Harbor, Me.…”
Section: Aind Materialsmentioning
confidence: 99%
“…The positive relationship observed between the increased stressing conditions and the increasing frequency of MN might support the hypothesis of association of continuous altered environmental factors (temperature oscillation, noise and photoperiod) and genomic damaging. Several authors have suggested stress as an induce genoto‐xic damage, both at the chromosomal and the molecular levels (Adachi, Kawamura, & Takemoto, 1993; Ciaranello, Dornbusch, & Barchas, 1972; Fischman, Pero, & Kelly, 1996; Glaser, Thorn, Tarr, Kiecolt‐Glaser, & D'Ambrosio, 1985; Kiecolt‐Glaser, Stephens, Lipetz, Speicher, & Glaser, 1985) and the present research seems to corroborate such previous results by new environmental‐based associations with a progressive chromosome damage on peripheral blood cells of Rattus norvegicus .…”
Section: Discussionmentioning
confidence: 99%